Pengabdian Masyarakat Tentang Penanganan Udang Windu Segar di Pasar Ikan Kedonganan Bali - I Gde Suranaya Pandit; I Wayan Wesna Astara; Pande Ayu Naya Kasih Permatananda (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2022)
Badung Regency Bali is one of the regencies in Bali that has a landing site, fresh fish marketing, and culinary tourism in the form of cafes and restaurants based on fish and other fishery products such as shrimp, squid, various shellfish, and others. All fishery-based community activities in Kedonganan Fish Market are mostly under the Mina Segara Village Unit Cooperative (KUD). One of the problems experienced by traders in Kedonganan Fish Market is the low level of sanitation that causes the quality of shrimp as a raw material that is often in demand by the public to be of low quality. The purpose of this activity is to improve the understanding of fish traders on how to handle fresh tiger shrimp to maintain fresh tiger shrimp products. The activities offered include training on how to handle fresh tiger shrimp using the cold chain system method, counseling on the legal aspects of market arrangement that meets the principles of ecotourism, and trader health. This service activity was carried out in the hall of KUD Mina Segara Kedonganan Village for 2 days including socialization of activities, training and demonstration of fresh tiger shrimp handling plots, delivery of boxfiber assistance, provision of PPE, and making Kedonganan Fish Market masterplan. The results of the activity are assessed from the input, outcome, and output indicators which are quite good, so it is necessary to be carried out continuously in the future.